The Effect of Organizational Justice on Stress with Work-Family Conflict as a Mediating Variable - wandarujati, Maximilian; Nufitri, Titi; Anggraeni, Ade Irma (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2020)
The purpose of this study is to analyze the effect of organizational justice on Tupperware member stress with work-family conflict as a mediating variable. There were 80 member chosen as respondent of the study by using purposive sampling method. This study applies quantitative approach. Analysis tool used in this research is Multiple Regression with SPSS software. Based on the result of the analysis, it can be concluded that organizational justice has negative effect on on Dito Mulyo Pangestu Tupperware member stres with work-family conflict as a mediating variable.